Causes and impacts of domestic violence against women in Tikapur (Journal of Tikapur Multiple Campus, 2015)
The present study on "main cause and Impact of domestic Violence against women in Tikapur Municipality was undertaken in the backdrop of report appearing in visual and written media depicting in human treatment to the women meted to them by their own family members. Only 10 women who are suffering from domestic violence were included in the study through purposive and snowball sampling method. the main objective of this study is to find out the main cause and impact of domestic violence against women the study finding that domestic violence in the study areas was found among women of all age groups. According to the patriarchal norms and low status of women did not prepared even old women more than 45 years from being a victim of violence Illiteracy teenage marriage, low economic status as well as religious norms and values are the main cause of violence. Respondents are suffering from physical, mental emotional and sexual violence and it carried different kinds of problems like. Physical mental and reproductive health problems and negative health behaviors are seen in the study area.